Assessing the Selectivity of FXR, LXRs, CAR, and RORγ Pharmaceutical Ligands With Reporter Cell Lines - Toporova, Lucia; Grimaldi, Marina; Boulahtouf, Abdelhay; Balaguer, Patrick (Frontiers in Pharmacology, 2020)
To characterize nuclear receptor (NR) specificity of synthetic pharmaceutical chemicals we established stable cell lines expressing the ligand binding domains (LBDs) of human FXR, LXRα, LXRβ, CAR and RORγ fused to the yeast GAL4 DNA binding domain (DBD). As we have already done for PXR, a two-step transfection procedure was used. HeLa cells stably expressing a Gal4 responsive gene (HG5LN cell line) were transfected by Gal4-NRs expressing plasmids. At first, using these cell lines as well as the HG5LN PXR cells, we demonstrated that the basal activities varied from weak (FXR and LXRs), intermediate (PXR), to strong (CAR and RORγ), reflecting the recruitment of HeLa co-regulators in absence of ligand. Secondly, we finely characterized the activities of commercially available FXR, LXRα, LXRβ, CAR, RORγ and PXR agonists/antagonists GW4064, feraxamine, DY268, T0901317, GW3965, WAY252623, SR9238, SR9243, GSK2033, CITCO, CINPA1, PK11195, S07662, SR1078, SR0987, SR1001, SR2211, XY018, clotrimazole, dabrafenib, SR12813 and SPA70, respectively. Among these compounds we revealed both, receptor specific agonists/antagonists, as well as less selective ligands, activating or inhibiting several nuclear receptors. FXR ligands manifested high receptor selectivity. Vice versa, LXR ligands behaved in non-selective manner, all activating at least PXR. CAR was selectively influenced by their ligands, while it also responded to several LXR ligands. Finally, although PXR was quite selectively activated or antagonized by its own ligands, it responded to several NRs ligands as well. Thus, using these reporter cell lines enabled us to precisely characterize the selectivity of pharmaceutical ligands for different nuclear receptors.